(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The social and emotional development of preschool children is one of the pressing problems of modern pedagogy and educational psychology. Socialization of preschool children is carried out through communication and consistent interactive activities. In this process, qualities such as initiative, flexibility, emotions and sensitivity determine the content and level of children’s communication. The article analyzes the problems associated with this issue, past and current educational and psychological research in the context of social demands, as well as recommendations for role-playing games and their use, which are important for further improving the socio-emotional development of preschool children.